2021
DOI: 10.1111/dmcn.15099
|View full text |Cite
|
Sign up to set email alerts
|

Visual field defects after vigabatrin treatment during infancy: retrospective population‐based study

Abstract: ABBREVIATIONS OCTOptical coherence tomography RNFL Retinal nerve fiber layer TSC Tuberous sclerosis complex VAVFD Vigabatrin-attributed visual field defect AIM To investigate the prevalence of vigabatrin-attributed visual field defect (VAVFD) in infantile spasms and the utility of optical coherence tomography (OCT) in detecting vigabatrin-related damage. METHOD We examined visual fields by Goldmann or Octopus perimetry and the thickness of peripapillary retinal nerve fiber layer (RNFL) with spectral-domain OCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…Vigabatrin is contraindicated in the case of adverse effects on the visual field. Jonsson et al evaluated the effects on long-term visual field in children who received vigabatrin and found the risk of developing ocular side effects at a rate of 31% with the use of vigabatrin in children for more than 6 months (17) . Biswas et al reported retinal toxicity rate of 29% in patients who were diagnosed with epileptic spasm and were using vigabatrin (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Vigabatrin is contraindicated in the case of adverse effects on the visual field. Jonsson et al evaluated the effects on long-term visual field in children who received vigabatrin and found the risk of developing ocular side effects at a rate of 31% with the use of vigabatrin in children for more than 6 months (17) . Biswas et al reported retinal toxicity rate of 29% in patients who were diagnosed with epileptic spasm and were using vigabatrin (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Vigabatrin is an antiepileptic used in the treatment of seizure disorders in childhood and adulthood. It has the potential to cause irreversible dose-dependent [ 37 ] visual field loss, which led to its FDA approval being accompanied by a mandatory Risk Evaluation and Mitigation Strategy program. While not fully understood, vigabatrin-associated visual field loss (VAVFL) is thought to occur as a result of toxicity to retinal photoreceptor and ganglion cells [ 38 ].…”
Section: Vigabatrinmentioning
confidence: 99%
“…Heute wird Vigabatrin (Antikonvulsivum für schwere Epilepsien vor allem bei Kindern) nur noch bei Fehlen anderer Therapiemöglichkeiten eingesetzt. Unter Therapie können irreversible konzentrische Gesichtsfeldeinschränkungen auftreten [29]. Zur Früherkennung einer beginnenden Schädigung ist ein Ganzfeld-ERG einsetzbar, im Verlauf zeigt sich eine Reduktion der Nervenfaserschicht in der OCT. Eine Therapieänderung ist mangels Alternativen meist nicht möglich.…”
Section: Intraretinale Transmissionsstörungenunclassified